Gaya Kepemimpinan Demokrasi pada Komisi Remaja dan Pemuda Gereja Bethel Indonesia di Kecamatan Baguala Kota Ambon - Jusuf H Kelelufna (IAKN Ambon, 2018)
Problems in applying democratic leadership style in the youth and youth committee of GBI in the Baguala sub-district of Ambon city, can be seen in terms of delegation of tasks not accompanied by delegation of authority, program planning tendencies not formulated together, and low involvement of youth and youth members in each activity DPA. This study aims to measure how much the democratic leadership style variable at the GBI youth and youth commission in Baguala sub-district, Ambon City consists of indicators; Member Participation, Member Control, and Award for Members, viewed from various categories of respondents' backgrounds, namely: gender, marital status, age, service category and KPA. This study uses a quantitative method with descriptive data analysis then the data per indicator is cross-analyzed with various background categories. The results showed that the Leadership Style of Democracy in the Youth and Youth Commission of the Indonesian Bethel Church in Baguala District, Ambon City, according to respondents, was done well, which was 81.5% than expected. The highest rating according to respondents is on the indicator of respect for members that is equal to 83.5% followed by indicators of member control at 82.4%, on the contrary the lowest rating on the indicators of Member Participation is 79.5%. Cross-analysis with various background categories shows that the tendency of involvement of older members is far more dominant than younger members.